Geomorphic constraints on differential surface uplift across the Dien Bien Phu Fault, northwestern Vietnam, and its implications on crustal dynamics in the southeastern Tibetan Plateau - Thi-Hue Dinh; Chih-Tung Chen; Yu-Chang Chan (Geoscience Letters)
Abstract At the southeastern frontier of the propagating India–Asia collision, the Dien Bien Phu Fault in northwestern Vietnam provides a good opportunity to study the growth and crustal dynamics of the Tibetan Plateau; however, full activity of the fault remains poorly constrained, particularly the vertical component. This study offers, for the first time, new constraints on surface uplift pattern across the fault based on quantitative tectonic geomorphology analyses (normalized steepness index, and erosion rate from fluvial shear stress) combined with mapping of river terraces. The results from geomorphic indices exhibit a conspicuous concurrence between regions of high normalized steepness index and of high erosional rate values that are spatially concentrated on the W/NW side of the Dien Bien Phu Fault. The results from the preliminary terrace mapping are also consistent with the spatial trends of the geomorphic indices, indicated by the larger elevation separations between terrace levels on the W/NW side of the fault. Since non-tectonic factors including climate and lithology do not systematically vary across the Dien Bien Phu Fault, such spatial consistence indicates a significant higher uplift on the W/NW side of the fault. Considering that the observed uplift is not concentrated near the fault trace but distributed in the whole fault block, we postulate crustal thickening in the W/NW side of the Dien Bien Phu Fault through arrival of ductile mid-to-lower crust flow propagating from the Tibetan Plateau.